The Effect Of Ultraviolet Light Treatment In Extend Shelf Life And Preserve The Quality of Strawberry (Fragaria x ananassa) cv. Festival - Mohd Idris Nor Idzwana; Khor Sen Chou; Ramisah Mohd Shah; Norhidayah Che Soh (Food, Agriculture and Natural Resources - NETWORKS, 2020)
Strawberry (Fragaria x ananassa) is a highly perishable product and rarely to be kept for more than 7 days. Cold chain system is the only methods apply in Malaysia strawberry industry to prolong the shelf life and preserve the quality of strawberry. UV light treatment proved to be effective in inhibit microbial loads and delay ripening process of fruit products where short wavelength (254 nm) ultraviolet-C was proved in keeping the freshness and quality of fruits or vegetables. This experiment was conducted to determine the effect of UV-C irradiation on extending shelf life and to determine the optimum radiation intensity of UV-C treatment on postharvest quality of treated strawberry. A total of 399 of strawberries cv. Festival were harvested in red colour with maturity stage of >80 – 85% from Cameron Highlands’s strawberry farm. The strawberries were exposed to different doses (0, 0.5, 0.6, 0.7, 0.8, 0.9 and 1.0 kJ/m2) of ultraviolet-C (254nm, UV-C) radiation. The treated strawberries were randomly placed in the polystyrene trays and stored in the dark chilling room at -5Cº for 9 days. The significant differences were found when the highest level of dosage was applied. UV-C treated strawberries with the highest doses (1.0 kJ/mº) are significantly firmer (0.557N), higher total soluble solids content (7.5 ºBrix) and ascorbic acid contain (0.518mg/ml) on day 9 (p